Impact of a population‐wide mental health promotion campaign on people with a diagnosed mental illness or recent mental health problem - Rob Donovan; Geoffrey Jalleh; Katy Robinson; Chad Lin (Elsevier, 2016)
Abstract Objectives: To determine the impact of the Act‐Belong‐Commit mental health promotion campaign on people with a diagnosed mental illness or who had sought professional help for a mental health problem in the previous 12 months. Method: In 2013 and 2014, 1,200 adults in Western Australia were interviewed by telephone. The questionnaire measured campaign reach, impact on beliefs about mental health and mental illness and behavioural impact. Results: Campaign impact on changing the way respondents thought about mental health was significantly higher among those with a mental illness or who had sought help (41.4% vs 24.2%; p<0.001), as was doing something for their mental health as a result of their exposure to the campaign (20.5% vs 8.7%; p<0.001). Conclusions: The campaign appears to empower people with a mental illness or who recently sought help to take steps of their own to enhance their mental health.